THE ROLE OF ISLAMIC EDUCATION IN SHAPING SOCIAL IDENTITY IN CONTEMPORARY MUSLIM SOCIETIES - Mahfud, Muhammad; Zulfa, Laila Ngindana; Karima, Qonita; Ali, Makhrus; Thai, Aom (Yayasan Adra Karima Hubbi, 2026)
Islamic education has long served as a central institution for transmitting religious knowledge, moral values, and collective norms within Muslim societies. In contemporary contexts marked by globalization, social diversity, and identity contestation, the role of Islamic education in shaping social identity has gained renewed scholarly attention. This study aims to examine how Islamic education contributes to the formation of religious identity, social belonging, and civic orientation in contemporary Muslim societies. The research employed a quantitative cross-sectional design involving students from Islamic educational institutions across diverse social settings. Data were collected using validated questionnaires measuring educational exposure, religious identity, ethical orientation, and social engagement, and were analyzed through descriptive and inferential statistical techniques. The findings indicate that Islamic education significantly influences social identity formation by strengthening religious self-understanding, promoting shared moral values, and fostering a sense of communal belonging. Positive associations were also found between Islamic education and civic engagement, suggesting an integrative identity orientation rather than social withdrawal. The study concludes that Islamic education functions as a multidimensional socializing process that mediates between religious tradition and contemporary social realities.